The outcome of elderly patients with advanced urothelial carcinoma after platinum-based combination chemotherapy - Bamias, A.; Efstathiou, E.; Moulopoulos, L.A.; Gika, D.; Hamilos, G.; Zorzou, M.P.; Kakoyiannis, C.; Kastritis, E.; Bozas, G.; Papadimitriou, C.; Dimopoulos, M.A. (Annals of Oncology, 2005)
Background: The majority of patients with advanced urothelial cancer are elderly, but data regarding this specific age group are limited. We compared the tolerability and efficacy of first-line platinum (cisplatin or carboplatin)-based chemotherapy in elderly patients (≥70 years) with those in younger patients. Patients and methods: A total of 381 patients with advanced urothelial carcinoma received CIMV (cisplatin, ifosphamide, methotrexate, vinblastine) (n=32), MVAC (methotrexate, vinblastine, doxorubicin, cisplatin) (n=105), DC (docetaxel, cisplatin) (n=174), CaG (carboplatin, gemcitabine) (n=64) or other regimes (n=6) and were included in this analysis. Results: A total of 116 patients were ≥70 years. Elderly patients experienced more frequent neutropenia grade 3/4 (55% versus 37%, P=0.087) and renal toxicity (28% versus 10%, P=0.033) among patients treated with CIMV/MVAC, and neutropenic infections (4% versus 0%, P=0.019) among patients treated with DC. Median survival did not differ significantly between elderly and younger patients (9.3 versus 10.5 months, P=0.16). Eastern Cooperative Oncology Group performance status (PS) and haemoglobin were independently associated with prognosis. Patients with PS <2 and haemoglobin ≥10g/dl had a median survival of 14 months as opposed to 5 months for patients with PS ≥2 or haemoglobin <10g/dl (P <0.001). Conclusion: Elderly patients with advanced urothelial cancer tolerate platinum-based chemotherapy well and derive the same benefit as their younger counterparts. © 2005 European Society for Medical Oncology.
Keywords: Bladder cancer; Chemotherapy; Elderly; Platinum